Ceratocystis wilt and canker – a disease that compromises the growing of commercial Acacia-based plantations in the tropics. (15th May 2019) - Nasution, A.; Glen, M.; Beadle, C.; Mohammed, C.
ABSTRACT: Ceratocystis wilt and canker disease has severely compromised the profitability of Acacia mangium plantations in Southeast Asia. The focus of this review is on Ceratocystis wilt and canker disease in Acacia trees. Its aim is to synthesise information about this fungal pathogen that can be used to inform development of suitable disease-control strategies in forest plantations. The last 20 years have seen many taxonomic changes in Ceratocystis, with some disagreement as to species boundaries. Therefore, an understanding of the origins and development of this disease requires reference to other species, particularly in the context of the biology and fungal taxonomy, disease symptoms and mechanisms of fungal dispersal. The risks and impacts of the disease on the sustainability of Acacia wood production are examined. Observing or surveying disease symptoms in plantations, selecting and planting tolerant or resistant Acacia trees, and the potential of endophytic bacteria as biological control agents are also included in this review.